Influence of water on rheology and strain localization in the lower continental crust. (29th July 2013) - Getsinger, A. J.; Hirth, G.; Stünitz, H.; Goergen, E. T.
Abstract : [1] We investigated deformation processes within a lower crustal shear zone exposed in gabbros from Arnøya, Norway. Over a distance of ∼1 m, the gabbro progresses from nominally undeformed to highly sheared where it is adjacent to a hydrous pegmatite. With increasing proximity to the pegmatite, there is a significant increase in the abundance of amphibole and zoisite (which form at the expense of pyroxene and calcic plagioclase) and a slight increase in the strength of plagioclase lattice‐preferred orientation, but there is little change in recrystallized plagioclase grain size. Phase diagrams, the presence of hydrous reaction products, and deformation mechanism maps all indicate that the water activity ( a H2O ) during deformation must have been high (∼1) in the sheared gabbro compared with the nonhydrated, surrounding host gabbro. These observations indicate that fluid intrusion into mafic lower crust initiates syn‐deformational, water‐consuming reactions, creating a rheological contrast between wet and dry lithologies that promote strain localization. Thus, deformation of lower continental crust can be accommodated in highly localized zones of enhanced fluid infiltration. These results provide an example of how fluid weakens lower continental crust lithologies at high pressures and temperatures. Key Points: Fluid and synkinematic reactions are important for strain localization Strain localization correlates with an increase in amphibole Deformation may be accommodated in highly localized zones of fluid infiltration